Structure and resistance in Thomas Pynchon's Bleeding edge - Grgas, Stipe (Array, 2020)
From his first to his last novel, Pynchon has addressed the “constraints” hemming in human existence and gestured to different ways of transcending these. After summarizing the way his novels exemplify this twofold movement I will offer a reading of his last novel Bleeding Edge and show how the dialectic between structures of power and human resistance continue to order the narrative. My reading of the novel will argue that, like in his previous work, the cooption of utopian potential resurfaces in this work and offers a vivid way of analyzing “speculative change” in literature.